Multidimentional Data Warehousing and mining - an Approach for Managing Multiple Reservoir Ecosystems - Nimmagadda, Shastri; Dreher, Heinz; Shtukert, O.; Zolotoi, N. (IEEE, 2013)
Many sedimentary basins comprise of numerous oil and gas fields. Each field has multiple oil and gas producing wells and each drilled well has multiple reservoir pay zones, with each pay zone having different fluids - either oil or gas and both. From a sedimentary basin scale, a super-type dimension is distinguished into its atomic and non-divisible dimensions, such as reservoir and structure. In database terminology, cardinality is representative of the set of elements-, and attributes and their relationships. Here, each element is interpreted as a dimension, narration of multiple dimensions for multiple elements within the context of a petroleum ecosystem. Ontology based cardinalities are described for designing constraints and business rules among multidimensional data models, to maintain integrity and consistency of the cardinalities. For the purpose of analyzing petroleum ecosystem and its reservoir connectivity, ontologies based cardinalities are described. Though sedimentary-basin ontology narrates, connectivity among structures, reservoirs, seals, source and other processes, such as migration and timing of occurrence or existence of these elements, but we focus on an approach exploring connections among multiple reservoirs and traps within a petroleum ecosystem. This approach minimizes the ambiguity during interpretation and management of reservoir ecosystems' limits or boundaries.